IMF's control of quasi-periodic ELF-VLF emissions - Yumoto, Kiyohumi; Sato, Natsuo (1985)
P(論文) Correlations among the magnitude of the interplanetary magnetic field (IMF), the modulation frequency of quasi-periodic (QP) ELF-VLF emissions observed at high-latitude conjugate-pair stations, Syowa Station (L∿6.1) in Antarctica and Husafell in Iceland, and the dominant frequency of low-latitude Pc 3 magnetic pulsations observed at Hermanus (L∿1.8) located near the Syowa Station's meridian in South Africa are examined by using the data obtained during the conjugate campaign in 1977. The analysis shows that the modulation frequency of type 1 QP emissions, QP's associated with Pc 3 magnetic pulsations, is correlated well with the IMF magnitude. On the other hand, it has been recently established that the frequency of compressional Pc 3 waves in the magnetosphere is also controlled by the IMF magnitude. These observational results support the phenomenological model that compressional magnetic waves originating upstream of the earth's foreshock modulate the type 1 QP emissions near the equatorial plane in the outer magnetosphere. departmental bulletin paper